Competence development as a driver of innovative and sustainable public procurement - Matin Taheriruh; Aki Jääskeläinen; Jakub Sieber (Journal of Public Procurement, 2026)
Purpose This study aims to examine how individual competence categories (enabling, procedural and relational) and their direct and indirect development are related to innovation, sustainability and operational performance in public procurement. Design/methodology/approach Survey data were collected from 173 public procurement professionals in Finland and the Netherlands. Using Consistent Partial Least Squares Structural Equation Modeling (PLSc-SEM), complemented by Necessary Condition Analysis (NCA), the study analyzes how competence development mechanisms are associated with individual competence levels and how these competences relate to performance outcomes. Findings Results show that relational competences have the strongest positive associations with innovation and operational performance, while procedural competences are positively related to operational and sustainability outcomes but show a non-significant, slightly negative association with innovation. Enabling competences are strongly related to procedural and relational competence levels. Both direct and indirect competence development mechanisms are positively related to competence levels, although the observed effects are moderate. Research limitations/implications While based on cross-sectional evidence, these results point to avenues for advancing understanding of how competence development relates to innovative and sustainable public procurement across institutional contexts. Social implications The findings highlight the importance of supporting complementary competence development through internal learning structures, while using external collaboration selectively as part of longer-term competence development efforts. Originality/value This study offers an empirical analysis of a holistic model linking competence development mechanisms to individual competence levels and performance outcomes in public procurement.